EVALUATING THE EFFECTIVENESS OF AUDIOVISUAL-BASED INFORMATION SERVICES IN PROMOTING STUDENT RESILIENCE - Fitri, Annisya; Daulay , Nurussakinah (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
This study aims to determine the effectiveness of information services using audio-visual media techniques in improving student resilience . This study uses a Quasi-Experimental approach, involving two groups (experimental group and control group), without randomization. The second group was given a Pre-Test and Post-Test to determine the effect of treatment oThis study aims to examine the effectiveness of information services using audio-visual media techniques in enhancing students' resilience at SMA Negeri 1 Palika. A quasi-experimental approach was employed, involving two groups (experimental and control) without randomization. Both groups were administered a pre-test and post-test to assess the impact of the treatment on the variables studied. The study population consisted of 48 eleventh-grade students at SMA Negeri 1 Palika, divided equally into a control group (n = 24) and an experimental group (n = 24), selected through purposive sampling. A resilience instrument adapted from Daulay (2024) was used to measure student resilience. Audio-visual media served as an engaging and interactive tool for delivering information. The results of the Independent Samples T-Test revealed that the post-test mean score of the control group was 86.67, while the experimental group achieved a higher post-test mean score of 96.88. A significant difference was found between the two groups (p-value = 0.001 < 0.05), indicating that the null hypothesis was rejected and the alternative hypothesis accepted. Therefore, it can be concluded that the use of audio-visual media in information services is effective in improving students' resilience.n the variables studied. The study population was 48 students of class XI SMA N I Palika divided into two groups, namely a control group of 24 people and an experimental group of 24 people, selected using the Purposive Sampling method. To measure resilience, a resilience instrument adapted by Daulay (2024) was used. Audio-visual media is used as a means of delivering interesting and interactive information. The results of the Independent Sample T-Test Post-Test for the Control Group (mean 86.67) while the results of the Post-Test for the Experimental Group (mean 96.88). This means that students who were treated with audio-visual media techniques were higher than the group that did not use audio-visual media techniques. And there is a significant difference between the control group and the experimental group (t = (P-Value) 0.001 < 0.05) then Ho is rejected and Ha is accepted. Thus, it can be concluded that the use of audio-visual media in information services is effective in increasing student resilience.